2022
DOI: 10.1177/23305517211060794
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic Microcapsules for Textile Materials by Spray Drying: Part 2—Exergy Analysis of Spray Drying Process

Abstract: In this study, the second part of a three-part series, exergy analysis of microencapsulation of photochromic dyes by the spray drying method was investigated. Since the spray dryers are thermal systems, energetic examination of the system components is an important issue for sustainable production with high efficiency. Exergy analysis is an important tool used in recent years for the analysis, design, and performance evaluation of thermal systems. The spray drying process was investigated considering two subsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It was indicated that the selected temperature of spray drying to produce microcapsules (120°C and 150°C of inlet temperatures) did not have a significant effect on color build up ( p < 0.05), which shows that the change in the microcapsule size (in the studied range for this study) did not affect coloration. In the previous study in which an exergy analysis was carried out for the production of photochromic microcapsules by spray drying, 40 it was concluded that the use of lower air inlet temperature resulted in a higher exergy efficiency. Therefore, since there is no difference in color build up, when the performance criterion is coloration, it will be more appropriate to use microcapsules produced at low air inlet temperature for sustainable production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was indicated that the selected temperature of spray drying to produce microcapsules (120°C and 150°C of inlet temperatures) did not have a significant effect on color build up ( p < 0.05), which shows that the change in the microcapsule size (in the studied range for this study) did not affect coloration. In the previous study in which an exergy analysis was carried out for the production of photochromic microcapsules by spray drying, 40 it was concluded that the use of lower air inlet temperature resulted in a higher exergy efficiency. Therefore, since there is no difference in color build up, when the performance criterion is coloration, it will be more appropriate to use microcapsules produced at low air inlet temperature for sustainable production.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, photochromic dye microcapsules produced under the conditions determined in previous studies 20,40 were applied onto cotton fabric by the pad–dry–cure process (capsule production parameters: feed rate = 3 mL/h; aspirator ratio = 95%; shell-to-core ratio = 2:1; water-to-ethanol ratio = 1/0.4; inlet temperature = 120°C and 150°C). Then, a consecutive washing process was applied to the fabrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation